Watermarking technique for wireless multimedia sensor networks: A state of the art - Potdar, Vidyasagar; Harjito, Bambang; Singh, Jaipal (ACM, 2012)
Wireless multimedia sensor networks (WMSNs) are an emerging type of sensor network which contain sensor nodes equipped with microphones, cameras, and other sensors that produce multimedia content. These networks have the potential to enable a large class of applications ranging from military to modern healthcare. Multimedia nodes are susceptible to various types of attack, such as cropping, compression, or even physical capture and sensor replacement. Hence, security becomes an important issue in WMSNs. However, given the fact that sensors are resource constrained, the traditional intensive security algorithms are not well suited for WMSNs. This makes the traditional security techniques, based on data encryption, not very suitable for WMSNs. Watermarking techniques are usually computationally lightweight and do not require much memory resources. These techniques are being considered as an attractive alternative to the traditional techniques, because of their light resource requirements. The objective of this paper is to present a critical analysis of the existing state-of-the-art watermarking algorithms developed for WMSNs.